Physics training teachers: physics teaching, STS approach and controversial issues - Luciano Fernandes Silva; Luiz Marcelo de Carvalho (Investigações em Ensino de Ciências, 2009)
We try in this paper to identify some difficulties that trainee Physic teachers had when dealing with controversial issues in their science teaching and their conceptions about Physics teaching. Trainee Physic teachers were invited to carry out science teaching activities in schools, exploring controversial subjects in their proposals. Data analysis pointed out that trainee teachers privileged in their teaching practices, science teaching activities experienced by themselves in their school life as well as in their under graduated courses. These results put in evidence the role of the experienced science teaching activities through out their school life as one of the main determinant factors in the process of constructing conceptions related to Physic teaching. These conceptions seem to be obstacles to the incorporation of controversial issues – considered as one of the methodological principles to contextualize contents of Physics in high schools.